Prevalence of enamel projections and its co-relation with furcation involvement in maxillary and mandibular molars: A study on dry skull - Prashant Bhusari; Ayushi Sugandhi; Sphoorthi Anup Belludi; Shoyab Khan (Wolters Kluwer Medknow Publications, 2013)
Background: The objectives of this study were to investigate the incidence of cervical enamel projection (CEP) in molars of Indian dry human skulls and to evaluate its relationship with furcation involvement (FI). Materials and Methods: The material consisted of 944 upper and lower first, second and third permanent molars from 89 Indian dry human skulls. CEPs were investigated from the buccal aspect of the tooth and classified according to a system describeddescribed by Masters and Hoskins. FI was measured horizontally from the buccal aspect into the furcation with a graduated probe to the nearest millimeter. Any measurement ≥2 mm was considered to have positive FI. Results: The results showed that CEPs was found more frequently in the mandibular than in the maxillary molars (2:1). The highest incidence of CEP was found in the mandibular second molar (14.7%) followed by the maxillary second molar (14.6%). The mandibular third molar showed the lowest incidence (5.5%). The association between CEP and FI (87.5%) was statistically significant. This favors the view of the possible role played by such anomalies in the progression of periodontal diseases. CEP in male skulls (77.4%) was significantly more prevalent than in female skulls (20.4%). No significant difference was found between the right and left side of maxillary and mandibular teeth with CEP and FI. Conclusion: The findings suggested the role of CEPs as a local contributing factor in localized chronic periodontitis and FI in molars. Detailed examination as well as early diagnosis of periodontal disease at the region of furcation is clinically very important.